Prognostic value of myocardial circumferential strain for incident heart failure and cardiovascular events in asymptomatic individuals: the Multi-Ethnic Study of Atherosclerosis - Choi, Eui-Young; Rosen, Boaz D.; Fernandes, Veronica R.S.; Yan, Raymond T.; Yoneyama, Kihei; Donekal, Sirisha; Opdahl, Anders; Almeida, Andre L.C.; Wu, Colin O.; Gomes, Antoinette S.; Bluemke, David A.; Lima, Joao A.C. (European heart journal, 2013)
Left ventricular (LV) circumferential strain (Ecc) is a sensitive index of regional myocardial function. Currently, no studies have assessed its prognostic value in general population. We sought to investigate whether Ecc has a prognostic value for predicting incident heart failure (HF) and other major cardiovascular events in asymptomatic individuals without a history of previous cardiovascular diseases. We, prospectively, assessed incident HF and atherosclerotic events during a 5.5 ± 1.3-year period in 1768 asymptomatic individuals aged 45-84 (mean age 65 years; 47% female) who underwent tagged magnetic resonance imaging for strain determination. During the follow-up period, 39 (2.2%) participants experienced incident HF and 108 (6.1%) participants had atherosclerotic cardiovascular events. Average of peak Ecc of 12-LV segments (Ecc-global) and mid-slice (Ecc-mid) was -17.0 ± 2.4 and -17.5 ± 2.7%, respectively. Participants with average absolute Ecc-mid lower than -16.9% had a higher cumulative hazard of incident HF (log-rank test, P = 0.001). In cox regression analysis, Ecc-mid predicted incident HF independent of age, diabetes status, hypertension, interim myocardial infarction, LV mass index, and LV ejection fraction (hazard ratio 1.15 per 1%, 95% CI: 1.01-1.31, P = 0.03). This relationship remained significant after adjustment for LV-end-systolic wall stress into covariates. In addition, by adding Ecc-mid to risk factors, LV ejection fraction, and the LV mass index, both the global χ(2) value (76.6 vs. 82.4, P = 0.04) and category-less net-reclassification index (P = 0.01, SE = 0.18, z = 2.53) were augmented for predicting HF. Circumferential strain was also significantly related to the composite atherosclerotic cardiovascular events, but its relationship was attenuated after introducing the LV mass index. Circumferential shortening provides robust, independent, and incremental predictive value for incident HF in asymptomatic subjects without any history of previous clinical cardiovascular disease. http://www.clinicaltrials.gov. Unique identifier: NCT00005487.